Effects of non-invasive brain stimulation on impulsivity in patients with mental disorders: a systematic review and meta-analysis of randomised clinical trials - Mariana Oliveira; Yuri de Castro Machado; Mateus Pereira Mundoca; Bernardo Viana; Debora Marques de Miranda; Marco Aurélio Romano-Silva (General Psychiatry, 2024)
Background Non-invasive brain stimulation (NIBS) techniques, such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS), may offer an alternative treatment strategy for impulsive behaviour. By modulating brain activity, these techniques could potentially enhance impulse control and mitigate impulsivity.Aims To provide a comprehensive analysis of the correlation between NIBS parameters, targeted brain regions and impulsivity.Methods We systematically searched PubMed, Scopus and Embase on 5 April 2023 for randomised controlled trials (RCTs) of NIBS on impulsivity. Unbiased Hedges’ g with 95% CIs was used to define the effect size. Cochran Q test and I² statistics were used to assess for heterogeneity; p values inferior to 0.10 and I²>25% were considered significant for heterogeneity. Publication bias was investigated by funnel plot analysis of point estimates according to study weights, by Egger’s regression test and by non-parametric rank correlation (Begg) test.Results A total of 18 studies were included, comprising 655 patients from 14 RCTs and four randomised crossover studies. The meta-analysis of effect sizes from 9 tDCS studies on impulsivity did not show a significant effect (g=−0.18; 95% CI −0.46 to 0.10; p=0.210) and from 9 repetitive TMS (rTMS) studies also did not yield a statistically significant effect (g=0.21; 95% CI −0.38 to 0.80; p=0.490). When analysing active tDCS using Barratt Impulsiveness Scale version 11, the scores showed a trend towards improvement with active tDCS over placebo (g=−0.54; 95% CI −0.97 to −0.12; p<0.05; I²=0%).Conclusions There is currently insufficient evidence to support the clinical use of rTMS or tDCS as a means of reducing impulsivity in individuals with mental disorders. The main limitations of this study are the lack of available patient-level data, a limited number of studies, the lack of consensus on the structure of impulsivity and variability in how impulsivity is measured and conceptualised.PROSPERO registration number CRD42023413684.